LINGUOCULTURAL FEATURES OF SYMMETRY AND ASYMMETRY PHENOMENA IN LITERARY TEXTS OF ENGLISH AND UZBEK LANGUAGES - Azimova Zilola Ismoil qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Introduction A literary text is not merely a source of aesthetic pleasure, but also a profound linguistic medium through which an author conveys their worldview, inner experiences, and cultural values. Literary discourse demonstrates the functional and aesthetic capacities of language, blending the author’s unique stylistic choices with culturally embedded expressive means. Artistic language employs a range of rhetorical devices—such as metaphor, simile, parallelism, gradation, and epithet—which enrich the text’s rhythm, imagery, and emotional depth. Among these, the phenomena of symmetry and asymmetry play a significant role in shaping the internal structure and aesthetic expressiveness of literary works. Analyzing how symmetry and asymmetry manifest in English and Uzbek literary texts offers deeper insight into the interconnection between language and culture, as well as into the aesthetic and semantic mechanisms that underlie different literary traditions.